RBC Exposure in Pediatric Extracorporeal Membrane Oxygenation: Epidemiology and Factors Associated With Large Blood Transfusion Volume*. Issue 8 (August 2018) - O'Halloran, Conor P.; Alexander, Peta M. A.; Andren, Kristofer G.; Mecklosky, Jessica; Salvin, Joshua W.; Larsen, Stephanie; Zalieckas, Jill; Fynn-Thompson, Francis; Thiagarajan, Ravi R.
Abstract : Objectives: To quantify and identify factors associated with large RBC exposure in children supported with extracorporeal membrane oxygenation. Design: Retrospective cohort study. Setting: Single tertiary care children's hospital. Patients: One-hundred twenty-two children supported with extracorporeal membrane oxygenation for greater than 12 hours during January 1, 2015, to December 31, 2016. Interventions: None. Measurements and Main Results: Clinical, laboratory, and survival data were obtained from medical records. Only data from patients' first extracorporeal membrane oxygenation run were used. The primary outcome was RBC volume exposure during extracorporeal membrane oxygenation (mL/kg/d). Patients with RBC exposure volume greater than 75th percentile were categorized as "high RBC use" patients. A "bleeding day" was identified if mediastinum or cannula sites were explored and/or Factor VIIa administration, gastrointestinal, pulmonary, or intracranial hemorrhages occurred. Median age was 0.3 years (interquartile range, 0–3 yr). Congenital heart disease ( n = 56; 46%) was the most common diagnosis. Median RBC volume transfused during extracorporeal membrane oxygenation was 39 mL/kg/d (interquartile range, 21–66 mL/kg/d). High RBC use patients were more likely be supported by venoarterial extracorporeal membrane oxygenation (100 vs 76%; p = 0.006), have congenital heart disease (68 vs 39%; p = 0.02), and experience bleeding (33 vs 11% d; p < 0.001). High RBC use patients showed a trend toward higher in-hospital mortality (58 vs 37%; p = 0.07). In the multivariable analysis, younger age (–9% per year; 95% CI, –10% to –7%; p < 0.001), more blood draws per day (+8%; 95% CI, 6–11%; p < 0.001), and higher proportion of bleeding days (+22% per 10% increase; 95% CI, 16–29%; p < 0.001) were associated with larger RBC exposure (model R 2 = 0.66). Conclusions: Bleeding during extracorporeal membrane oxygenation, frequent laboratory draws, and younger age were associated with increased RBC exposure during extracorporeal membrane oxygenation. Higher transfusion volume was associated with increased mortality.